The impact of corneal higher-order aberrations on dynamic visual acuity post cataract surgery - Wu, Tingyi; Wang, Yuexin; Li, Yuanting; Li, Yuanhong; Jiang, Xiaodan; Li, Xuemin (Frontiers in Neuroscience, 2024)
Purpose To explore the influence of corneal higher-order aberrations (HOAs) on dynamic visual acuity (DVA) post cataract surgery. Methods A total of 27 patients with 45 eyes following cataract surgery were included in this study. The postoperative monocular object-moving DVA at the velocity of 20, 40, and 80 degrees per second (dps) were examined at 1 month. The total corneal HOAs were measured with Scheimpflug-based corneal topography. The correlation between postoperative DVA and HOAs was analyzed. Results Significant difference was shown among DVA at different velocities (P < 0.001). The 20 dps DVA was significantly better than 40 (P < 0.001) and 80 (P < 0.001) dps DVA. No significant difference was observed between 40 and 80 dps DVA (P = 0.420). The vertical coma and the root mean square (RMS) of coma (RMScoma) were statistically correlated with 80 dps DVA (P < 0.05). The vertical trefoil, RMStrefoil and total RMSHOA were statistically correlated with 40 and 80 dps DVA (P < 0.05). The spherical aberration was not significantly associated with postoperative DVA (P > 0.05 for all velocites). The multivariate linear regression model revealed that age was a significant influential factor for 20 dps DVA (P = 0.002), and RMStrefoil (4 mm) and age were significantly associated with 40 and 80 dps DVA (P ≤ 0.01). Conclusion The research demonstrated that larger corneal HOAs, especially coma and trefoil aberrations were significantly associated with worse high-speed DVA, but not spherical aberration post cataract surgery.